2013
DOI: 10.1631/jzus.b1200311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium ferulate on preventing steroid-induced femoral head osteonecrosis in rabbits

Abstract: Abstract:The aim of this study is to investigate the effects and possible mechanisms of sodium ferulate (SF) on anti-apoptosis in steroid-induced femoral head osteonecrosis in rabbits. Japanese white rabbits were randomly divided into three groups (control group, treatment group, and model group), each with 24 rabbits. The model and treatment groups were first injected with an intravenous dose of horse serum, 10 ml/kg, three weeks later with an intravenous dose of 7.5 ml/kg, and two weeks later with an intramu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In a rabbit model of steroid-associated necrosis of the femoral head, our TUNEL assay results showed that apoptosis indeed existed in osteocytes and bone marrow cells in the early stage of glucocorticoid-induced femoral head osteonecrosis. In the study of Tian L et al, they observed the similar results [30]. Bcl-2 is an anti-apoptotic protein, but caspase-3 is a pro-apoptotic protein.…”
Section: Discussionmentioning
confidence: 59%
“…In a rabbit model of steroid-associated necrosis of the femoral head, our TUNEL assay results showed that apoptosis indeed existed in osteocytes and bone marrow cells in the early stage of glucocorticoid-induced femoral head osteonecrosis. In the study of Tian L et al, they observed the similar results [30]. Bcl-2 is an anti-apoptotic protein, but caspase-3 is a pro-apoptotic protein.…”
Section: Discussionmentioning
confidence: 59%
“…Bcl-2 and caspase-3 are typical apoptosisrelated factors. Bcl-2 was found to be up-regulated and caspase-3 was found to be down-regulated during the development of SANFH (39). Intriguingly, HIF-1α appears to regulate numerous pro-apoptotic proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In another study total serum cholesterol and triglyceride levels were found signifi cantly higher in animals with ONFH compared to controls 35) . Pritchett showed that statins reduce the incidence of osteonecrosis in 284 patients treated with high-dose steroid 37) .…”
Section: Pt Aptt and Inr Resultsmentioning
confidence: 87%
“…Many drugs; pravastatin, sodium ferulate ,warfarin, low-molecularweight heparin, statins, vitamin E, naringin and salidroside have been tested, resulting in prevention or suppression of steroid-induced ONFH 3,[33][34][35][36][37][38] . However, to the best of our knowledge, there is no study reported in the literature, so far evaluating the eff ect of CAPE on steroid induced ONFH.…”
Section: Pt Aptt and Inr Resultsmentioning
confidence: 99%